Virtual School Tours: Boosting Community Interest and Attracting Prospective Students - Dewi, Annisa Tri Ananda; Alwahedi, Mohammad Abdul Aziz; Najiburohman, Najiburohman; Hefniy, Hefniy; Hasan Agus R., Abu (Evaluasi: Jurnal Manajemen Pendidikan Islam, 2025)
This study aims to understand the role of Virtual School Tours (VSTs) in helping schools expand their information reach, present their facilities more persuasively, increase data transparency, and strengthen relationships with prospective students. The study employed a qualitative approach. Data were obtained through in-depth conversations with school officials, direct observation of various digital platforms used for publication, and document searches related to the dissemination of school information. The research findings indicate that VSTs enable the public to gain an overview of the school without having to physically attend, thus making access to information easier and more inclusive. The presentation of facilities through videos and digital tours provides a more vivid picture of the school's strengths. Information transparency increased because the data displayed on official channels was more organized and easily accessible. Furthermore, interaction with prospective students increased along with the increase in responses.